THE SEISMIC PROCESS IN THE FREQUENCY RANGE 0.05-0.5 MHZ: PATTERNS AND PECULIARITIES - Petrova L.N. (My University, 2000)
Information is given on the recording instruments and the principles of the method used for a structural analysis of recorded seismic motion. Statistical spectra of the process and the time series characterizing the variation of its intensity are presented. The long-period seismic process was analyzed qualitatively in relation to seismicity. The phenomenon of pulsations recorded before the May 1995 Sakhalin earthquake is illustrated. This study suggests that the seismic process under study reflects the dynamics of Eurasian continental plate motion.